Apoptosis Related Human Wharton's Jelly-Derived Stem Cells Differentiation into Osteoblasts, Chondrocytes, Adipocytes and Neural-like Cells-Complete Transcriptomic Assays - Stefańska, Katarzyna; Nemcova, Lucie; Blatkiewicz, Małgorzata; Pieńkowski, Wojciech; Ruciński, Marcin; Zabel, Maciej; Mozdziak, Paul; Podhorska-Okołów, Marzenna; Dzięgiel, Piotr; Kempisty, Bartosz (International journal of molecular sciences, 2023)
Wharton's jelly-derived mesenchymal stem cells (WJ-MSCs) exhibit multilineage differentiation potential, adhere to plastic, and express a specific set of surface markers-CD105, CD73, CD90. Although there are relatively well-established differentiation protocols for WJ-MSCs, the exact molecular mechanisms involved in their in vitro long-term culture and differentiation remain to be elucidated. In this study, the cells were isolated from Wharton's jelly of umbilical cords obtained from healthy full-term deliveries, cultivated in vitro, and differentiated towards osteogenic, chondrogenic, adipogenic and neurogenic lineages. RNA samples were isolated after the differentiation regimen and analyzed using an RNA sequencing (RNAseq) assay, which led to the identification of differentially expressed genes belonging to apoptosis-related ontological groups. ZBTB16 and FOXO1 were upregulated in all differentiated groups as compared to controls, while TGFA was downregulated in all groups. In addition, several possible novel marker genes associated with the differentiation of WJ-MSCs were identified (e.g., SEPTIN4, ITPR1, CNR1, BEX2, CD14, EDNRB). The results of this study provide an insight into the molecular mechanisms involved in the long-term culture in vitro and four-lineage differentiation of WJ-MSCs, which is crucial to utilize WJ-MSCs in regenerative medicine.
Keywords: buněčná diferenciace; proteiny nervové tkáně; Humans; Nerve Tissue Proteins; mesenchymal stem cells; osteoblasty; MSC; lidé; Osteoblasts; Cells, Cultured; apoptosis; chondrocyty; differentiation; apoptóza; Adipocytes; Whartonův rosol; tukové buňky; Mesenchymal Stem Cells; Wharton Jelly; mezenchymální kmenové buňky; kultivované buňky; Cell Differentiation; transkriptom; Transcriptome; Wharton’s jelly; RNAseq; Chondrocytes; Apoptosis